"GEOGRAPHY OF FLAGS" OF THE MODERN WORLD STATES (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The article examined the geographical features of the formation of the flag system of the modern world. As a result, it was established that the first flags had the same combination of colors – white, blue, red. Later flags that emerged can be divided into "continuation flags" and "contrasting flags", but both "continuation flags" and "contrasting flags" relied on earlier flags. Without taking into account the historical and geographical context of the emergence and use of flags, their study hardly makes sense. Identifying this context is itself a very difficult task. What comes out in the end is not always conclusive, but it is always interesting.
Keywords: geography; vexillology; heraldry; flags; states